The Report Alignment Analysis of Regional Property to Local Government Financial Reports as Preparation for Implementation of Permendagri Number 77 of 2020 (Case Study in Bintan District Government) - Muhammad Isa Alamsyah; Muhammad Isa Alamsyahbana; Novi Chandra Saputra; Meidi Yanto; Armansyah Armansyah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Public accountability is the obligation of the regional government, in this case the Regional Head as the mandate holder from the community, to convey accountability for all activities and funding during the fiscal year period in the form of a report and explain it to community representatives, in this case the DPRD, which is then agreed upon as a regional legal product. Regional Government Financial Reporting consists of 7 (seven) types of reports, namely Budget Realization Reports, Reports on Changes in Budget Overbalances, Cash Flow Reports, Operational Reports, Reports on Changes in Equity, Balance Sheets and Notes to Financial Statements. Furthermore, the benefit of this writing is to become a reference for executors preparing local government financial reports in compiling and harmonizing Regional Property Reports and Regional Government Financial Reports. In addition, several implementative steps will be given in this alignment. The results in this writing are that in the Management of Regional Property which includes the Administration of Regional Property must still refer to the applicable regulatory provisions and implementative steps in this alignment, namely by preparing SOPs for Administration of Regional Property, compiling and preparing Manual Working Papers As Material for Implementing Regional Property Reconciliation, verifying and correcting expenditures where budgeting errors occur and conducting BIMTEK as well as socializing guidance and performance monitoring of the User Property Management.